Utilization of Instagram social media in Managing Online Business for MSMEs - H Hanifa; Nevi Adjie Fitria; Yulia Puspa; Arjuna Rizaldi (Universitas Komputer Indonesia, 2021)
This research aims to analyse the utilization of Instagram social media in the online business marketing of MSMEs @kunyeman_. This research uses descriptive qualitative research methods. The data collection techniques used are observation, interview, and documentation studies. The technique of determining the sample is technical purposive sampling. The study was conducted in February 2022 online. With the results of research that @kunyeman_ has used Instagram social media in managing his business. Because @kunyeman_ play an active role in marketing through Instagram social media to expand market reach and increase purchases. Social media is a medium to socialize with each other and is done online that allows humans to interact without being limited to space and time. One of the most commonly used social media is Instagram. Instagram is one of the most popular apps among social media users. Instagram can be used as one of the strategies in MSME marketing, especially MSMEs @kunyeman_. Instagram has a positive impact on small businesses @kunyeman_ because it can increase sales, expand marketing, and increase sales.